2019
DOI: 10.1111/jfpp.14355
|View full text |Cite
|
Sign up to set email alerts
|

Improving oxidative stability of flaxseed oil with a mixture of antioxidants

Abstract: The optimum combination of antioxidants used for stabilization of flaxseed oil and extension of its shelf life was examined. To achieve this goal, based on different antioxidant mechanisms, a combination of four types of antioxidants including tocopherol, ascorbyl palmitate (AP), phytic acid (PA), and a source of polyphenol (antioxidant of bamboo leaves (AOB), rosemary extract (RE), tea polyphenols extract (TP), and tea polyphenol palmitate (TPP)) were added to flaxseed oil. The effects were monitored using pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…The obvious changes of POV and TBARS values in salted meat with PNE might be attributed to its high content of polyphenols. It has been reported that polyphenols exhibit the electron delivery capability to terminate the free radical chain reactions (Lu et al., 2019) so as to attenuate the lipid deterioration of meat. In addition, pine needles of C. deodara are also observed to inhibit the growth of spoilage bacteria in food (Zeng et al., 2012), which show the potential value to protect food quality and safety during food processing and preservation.…”
Section: Resultsmentioning
confidence: 99%
“…The obvious changes of POV and TBARS values in salted meat with PNE might be attributed to its high content of polyphenols. It has been reported that polyphenols exhibit the electron delivery capability to terminate the free radical chain reactions (Lu et al., 2019) so as to attenuate the lipid deterioration of meat. In addition, pine needles of C. deodara are also observed to inhibit the growth of spoilage bacteria in food (Zeng et al., 2012), which show the potential value to protect food quality and safety during food processing and preservation.…”
Section: Resultsmentioning
confidence: 99%
“…Among these prooxidants, the temperature has a more significant effect on oil autoxidation because elevated temperature accelerates fatty acids oxidation rate by decomposing the hydroperoxides into products such as organic acids, alcohols, aldehydes, and ketones (Vaidya & Eun, 2013). Temperature dependence of seed oil autoxidation has been reported in several studies on oils, including walnut, grape, and flaxseed oil (Lu et al, 2020;Vaidya & Eun, 2013). These studies have demonstrated that oil oxidation indices increase with elevation in temperature.…”
Section: Practical Applicationsmentioning
confidence: 97%
“…The Arrhenius equation is the most common model for shelf-life determination in foods on account of its ability to create a specific relationship between the temperature and reaction rate constant (Conte et al, 2020;Kurtulbaş et al, 2018). Elhussein et al (2018) and Lu et al (2020) studied the lipid oxidation kinetics of sesame and flaxseed oil, respectively using the Arrhenius equation and activated complex theory and calculated kinetic parameters such as the rate constant (k), energy for activation (E a ), enthalpy (ΔH ‡ ), entropy (ΔS ‡ ) and Gibbs-free energy (ΔG ‡ ). However, the application of the Arrhenius model to determine the oxidation kinetics, thermodynamics, and shelf life of oil from pretreated seeds is limited.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Thus, a suitable improvement to the novel plant-based meat alternatives could be to consider the use of high ALA oils, rich in ω-3, instead of high LNA oils rich in ω-6 fatty acids. An important consideration is that high ALA oils are more prone to lipid oxidation (and perhaps represents a reason why high LNA oils are typically used in meat substitutes); however, the addition of natural anti-oxidants (Wang et al, 2018;Lu et al, 2020) as well as entrapment of high ALA oils with isolated plant proteins (Karaca et al, 2013;Bajaj et al, 2015) represent worthwhile opportunities to explore for producers of plant-based meat substitutes that consider the use of high ALA oils in their products, which potentially increases their healthfulness.…”
Section: Essential Fatty Acidsmentioning
confidence: 99%